Potential transfer of organic pollutants from littoral plastics debris to the marine environment. (May 2018) - León, Víctor M.; García, Inés; González, Emilia; Samper, Raquel; Fernández-González, Verónica; Muniategui-Lorenzo, Soledad
Abstract: Plastic polymers act as passive samplers in air system and concentrate hydrophobic organic contaminants by sorption or specific interactions, which can be transported to other systems such as the marine environment. In this study plastic debris was sampled in the surrounding area of a Mediterranean lagoon in order to determine the concentration of persistent and emerging organic contaminants. More specifically, desorption of 91 regulated and emerging organic contaminants (polycyclic aromatic hydrocarbons, polychlorinated biphenyls, organochlorinated pesticides, current-use pesticides, personal care products, other pesticides and plastic additives) was characterized for the first 24 h from different polymers to seawater and the remaining content of these contaminants was also extracted by ultrasonic extraction with methanol. All samples were analyzed by Stir Bar Sorptive Extraction coupled to GC/MS. A significant fraction of sorbed contaminants in polymers was desorbed in the first 24 h, particularly for triazines and organophosphorus pesticides due to their lower hydrophobicity than other considered analytes. The remaining contaminants contained in plastics can be also transferred to seawater, sediments or biota. Considering 24 h desorbed fraction plus the remaining methanol extracted fraction, the highest transfer levels corresponded to personal care products, plastic additives, current-use pesticides and PAHs. This is the first study to show the relevance of the transport of organic contaminants on plastic debris from littoral areas to the marine environment. Graphical abstract: Image 1 Highlights: Plastics accumulated regulated and emerging organic contaminants from the environment. Less hydrophobic contaminants were mainly desorbed(>30%) from plastics to seawater. PAHs, triazines and other pesticides were the most commonly detected contaminants. PAHs and personal-care products were the predominant pollutants retained by plastic. Potential contribution of organic contaminants from plastics to the coastal areas. Abstract : The least hydrophobic organic contaminants are partially desorbed from littoral plastics to seawater in 24 h and the rest of sorbed contaminants can be transferred to other compartments.